Pengaruh E-Satisfaction Terhadap Continuance Intention Pada Pengguna Aplikasi Akulaku - Aria Dewi Septiani; Samuel Indra Marcelino; Abdul Yusuf (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2022)
This study was conducted to determine the effect between variables in predicting the intention to continue using e-satisfaction as an intervening variable. The variables in this study include continuance intention, e-satisfaction, online informative motivation, and online service. Data collection techniques have been carried out by distributing online questionnaires to 100 respondents using the Akulaku application. The analytical method used is path analysis using SPSS 25.0 software. The results show that electronic satisfaction has a positive effect on user intention to continue and as a mediating variable satisfaction also mediates the relationship between online informative motivation and online services on sustainability intentions. This research also adds to the limitations and suggestions for Akulaku and for further research